Legal issues related to the trading in agricultural real estate of the Treasury Agricultural Property Stock in the light of the amendment to the Act on management of agricultural property of the Treasury of 26 April 2019 - Iwaszkiewicz, Piotr (Przegląd Prawa Rolnego, 2020)
The article assesses the impact of the Act of 26 April 2019 amending the Act on shaping the agricultural system and certain other acts on trading in agricultural property of the Treasury Agricultural Property Stock. The amendment significantly changed the rules of managing agricultural property of the State Treasury carried out by the National Agricultural Support Centre. In particular, the changes concerned the organisation of restricted tenders aimed at supporting family agricultural holdings, strengthening the position of the tenant of the State Treasury agricultural land as well as the creation of agricultural production centers by the National Agricultural Support Centre. The author points out the practical consequences of the changes and formulates de lege ferenda conclusions.